2015
DOI: 10.1177/1088357615610547
|View full text |Cite
|
Sign up to set email alerts
|

Parent Perceptions About Autism Spectrum Disorder Influence Treatment Choices

Abstract: Parents of children with autism spectrum disorder (ASD) must identify, select, and even implement treatments. Child age, cognitive functioning, ASD symptoms, family income, parent education, and cultural background, all may influence treatment selection. Parents’ perceptions about ASD also may contribute. We explored whether parents’ perceptions of ASD, along with family- and child-specific characteristics, predicted use of various ASD treatment categories. Sixty-eight families from the Simons Simplex Collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Parents (13.2%) who received government subsidised treatment from schools or hospitals reported that the costs of the treatments were reasonable. Accessing school-based services is consistent with reports by Patten et al [27] and Mire et al [28]…”
Section: The Cost Involved In Various Treatments As Perceived By the supporting
confidence: 89%
“…Parents (13.2%) who received government subsidised treatment from schools or hospitals reported that the costs of the treatments were reasonable. Accessing school-based services is consistent with reports by Patten et al [27] and Mire et al [28]…”
Section: The Cost Involved In Various Treatments As Perceived By the supporting
confidence: 89%
“…For example, through visual maps, schedules and symbolic representation of events. (Mire, Gealy, Kubiszyn, Burridge, & Goin-Kochel, 2017). This category encompasses special diets, or dietary supplements, chelation, detoxification and interventions that are deemed helpful in addressing biomedical problems that have been suggested as linked to or underpinning autism.…”
Section: Introductionmentioning
confidence: 99%
“…Given the myriad of treatments available, it is not surprising that many families use multiple treatments [Bowker, D'Angelo, Hicks, & Wells, ; Green et al, ], implement them simultaneously [Goin‐Kochel, Myers, & Mackintosh, ], and start and stop various treatments throughout their child's life [Bowker et al, ]. Factors associated with parents' treatment selection include symptom presentation and child's age [Goin‐Kochel et al, ; Mire, Raff, Brewton, & Goin‐Kochel, ], parental education level and income [Patten, Baranek, Watson, & Schultz, ], geographic location [Murphy & Ruble, ; Mire, Hughes, Manis, & Goin‐Kochel, ], and parents' perceptions of treatment and ASD [Dardennes et al, ; Mire, Gealy, Kubiszyn, Backscheider‐Burridge, & Goin‐Kochel, ]. However, there are many unknowns about factors that influence parents' decisions to employ some treatments over others [Matson & Williams, ].…”
Section: Using Latent Class Analysis To Identify Treatment‐use Subgromentioning
confidence: 99%